Cyber Movement in India: Trends and Challenges - V. Basil Hans (International Journal of Information Security Engineering, 2025)
India’s digital transformation has led to a rapid expansion of its cyber ecosystem, making it one of the fastest-growing internet economies in the world. This digital revolution is marked by the growth of online infrastructure, a surge in internet users, and the integration of cutting-edge technologies such as AI, blockchain, and 5G. Yet, it also brings its own distinct challenges. Emerging trends such as the rise of digital payments, e-governance, and online education reflect India’s ambition to harness technology for economic growth and social inclusion. Simultaneously, the increase in cyberattacks, data breaches, and misinformation campaigns highlights the urgent need for robust cybersecurity frameworks, privacy regulations, and digital literacy initiatives. This study explores the key trends driving India’s cyber movement, including the role of public-private partnerships, the digital push under government initiatives like “Digital India”, and the growing startup ecosystem. It also explores issues like cybercrime, weak data protection regulations, and the gap in digital accessibility. By addressing these issues, India can navigate its path to becoming a secure and inclusive digital powerhouse. This analysis highlights the importance of striking a balance that promotes innovation while safeguarding security and fairness in the digital realm.
Keywords: Digital India; artificial intelligence; blockchain; cyber landscape; e-governance